Education and training of pedal harpists in Colombia and Spain in the twenty-first century - Mónica GALLEGO LÓPEZ (Ediciones Universidad de Salamanca, 2020)
This paper provides an approach to pedal harpist (teachers, interpreters and students) in Colombia and Spain, and offers a point of view of the harpist training in the twenty-first century. A cualitative approach is made to the harpist nowadays with the design, development, analysis and evaluation of interviews, and participation in important musical, cultural and pedagogical events around the pedal harp in the respective countries. Significant reflections on music education are offered, specially, different points of view on the harpist training and the profesional and educational development, becoming a pioneering study. The research shows the applications that critical history of the harp can be derived for education of harpist and the recognition of their value.